COVID-19 MANIFESTATION IN A CHILD WITH LUNG METASTASES OF OSTEOSARCOMA: A CASE REPORT - Yulwhinar Cego Saputra (Berkala Ilmiah Kedokteran Duta Wacana, 2021)
Background: COVID-19 (Corona virus disease-19) is an infectious disease caused by a new type of corona virus which in the same group of the virus that causes Severe Acute Respiratory Syndrome (SARS), where the incubation period for infection is 1-14 days or up to 24 days, accompanied by symptoms of a respiratory tract infection and other organ systems. The number of recent cases in November 2020 was 59.8 million worldwide. Elderly patients and people with comorbid diseases are at high risk of developing severe manifestations of this viral infection. Osteosarcoma is a deadly bone cancer that often causes patients to die from metastases to the lungs Purpose: The purpose of this study is to report cases of COVID-19 in a 9-year old child patient with a history of osteosarcoma at Bethesda Hospital Yogyakarta. Case Description: A 9-year old female patient came to the emergency room complaining of fever, cough, severe chest pain, and shortness of breath since 3 weeks before being admitted to the hospital. The patient had a past medical history of osteosarcoma since 1.5 years before being admitted to the hospital and an amputation procedure on the right arm was carried out, no specific illness in the family history was found. The general condition of the patient appears to be moderate with delirium consciousness (E4V6M1). Vital sign examination showed a pulse rate of 130 beats per minute, an oxygen saturation of 85% and a breath rate of 30 beats per minute. CT scan without contrast shows a massive left pleural effusion, malignancy/metastatic mass of the left lung, with pneumonic opacity in the right lung. Conclusion: COVID-19 is an infectious disease caused by SARS-CoV-2 and causes severe manifestations in patients with comorbid diseases including pulmonary metastases. CT-Scan modalities are used as a basis for diagnosis other than RT-PCR. Management of COVID-19 is in the form of supportive therapy based on the degree of disease severity.